Assessing potential spatial and temporal conflicts in Washington's marine waters. (August 2016) - Freeman, Mikaela C.; Whiting, Libby; Kelly, Ryan P.
Abstract: This paper uses spatial, temporal, and use-intensity data for 27 major marine uses in Washington waters to feature a method for assessing potential use conflicts in a variety of scenarios. The study represents a first step towards quantifying potential conflicts within Washington's Marine Spatial Planning (MSP) study area by using a cumulative analysis to highlight high- and low-use intensity areas and the novel Marine Potential Conflict Index (MPCI), which incorporates space, time, and intensity of use, to quantify pairwise potential conflicts between uses. About 10% of pairs of uses do not overlap spatially and are likely compatible with one another. Temporally, the number of uses peaks in July and August and falls during January and February. Additionally, the MPCI identified three important use types with a substantial degree of potential conflict: commercial fishing, tribal fishing, and shipping. External data were used in three cases to ground-truth the analysis, as a limited test of its utility in managing any potential conflict. This article assesses the extent of Washington's existing marine uses along spatial, temporal, and intensity axes, and more broadly provides a straightforward way to examine potential conflicts between marine uses. Highlights: A novel Marine Potential Conflict Index assesses potential conflict between uses. In Washington commercial fishing and shipping have substantial potential conflict. Empirical data coupled with MPCI scores identify conflicts to be resolved. First analysis of Washington current marine uses with space, time, and intensity.